College education in relation to business - Little, Bessie Belle (My University, 1891)
Introduction: In the early colonial days, in the history of America, where no schools worthy a mention existed in our own country, where few authors had advanced their works, and before a circulation of newspapers had begun, a person, in order to gain an education, must go across the waters, or, as the only alternative, he must remain ignorant. As civilization advanced and as the people became more enterprising, as their interests grew beyond the interest in their own little community, as manufactories sprung up and increased, it became necessary to satisfy the increasing demand for some means of general communication. This was provided for in the publication of newspapers. From this it was but a step to the publication of books. The supply increased, until, at the present time, our shops are literally overflowing with literature both of great and of minor importance. Since the founding of Harvard College our schools have kept pace with the general advancement of the people, and our school system compares well with that of the older continents.
Citation: Little, Bessie Belle. College education in relation to business. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Schools; Newspapers; Education; History; Theses; Manuscripts (documents)